1997
DOI: 10.1021/ma970675v
|View full text |Cite
|
Sign up to set email alerts
|

Ordered Diblock Copolymer Films on Random Copolymer Brushes

Abstract: Optical microscopy, neutron reflectivity, and small angle neutron scattering studies were used to investigate the structure of thin films of symmetric diblock copolymers of P(dS-b-MMA) as the interactions between the copolymer and the substrate were changed in a systematic manner. In cases where there was a strong preferential segregation of one of the components to the substrate, the lamellar microdomains were oriented parallel to the film surface. However, on a nearly neutral substrate, a mixed morphology wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
290
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(299 citation statements)
references
References 13 publications
(20 reference statements)
8
290
1
Order By: Relevance
“…Because the substrates are neutral, the cylindrical domains in P(S-b-MMA) block copolymer thin films orient predominantly perpendicular to the substrate surface. [50][51][52][53][54] Although the substrate is neutral to both blocks of the used P(S-b-MMA) copolymer, not all PMMA Figure 1. Schematic side view of the basic setup used in the in situ GISAXS experiment during sputter deposition.…”
Section: Resultsmentioning
confidence: 99%
“…Because the substrates are neutral, the cylindrical domains in P(S-b-MMA) block copolymer thin films orient predominantly perpendicular to the substrate surface. [50][51][52][53][54] Although the substrate is neutral to both blocks of the used P(S-b-MMA) copolymer, not all PMMA Figure 1. Schematic side view of the basic setup used in the in situ GISAXS experiment during sputter deposition.…”
Section: Resultsmentioning
confidence: 99%
“…Such approaches were pioneered by Mansky et al, who showed that the surface energies of polystyrene (PS) and polymethylmethacrylate (PMMA) homopolymers can be tuned by the use of a grafted layer of random copolymer P(S-r-MMA) with different chemical compositions of the monomers in the grafted chains. In this manner, they demonstrated that the grafted layers can furnish a neutral surface which is effective in creating perpendicularly aligned phases [6,7]. Subsequent work has advanced this idea to other systems by using alternative strategies such as crosslinking agents and/or grafting chemistries [2].…”
Section: Pacs Numbersmentioning
confidence: 99%
“…Indeed, grafted layers are soft substrates which can potentially modulate their thicknesses and/or allow for interpenetration to accommodate the morphology of selfassembly. Moreover, there is an underlying assumption that the surface energies of A and B homopolymers, usually determined through contact angle measurements, suffice to characterize the influence of interfacial interactions upon the self-assembly of the AB block copolymer [6][7][8]. However, such an assumption ignores the fact that the conformations and the energetics of block copolymers near grafted surfaces will depend explicitly on the self-assembled morphologies themselves, and can in general be different from the characteristics of the homopolymers.…”
Section: Pacs Numbersmentioning
confidence: 99%
“…This behavior has led to numerous experimental and theoretical studies of cylinder-forming copolymer thin films to try and develop a general strategy for annealing C ⊥ . Towards this end, Hawker and Russell et al made a significant contribution by introducing random copolymer brushes grafted to wafer substrates, creating a neutral mean-field environment for the copolymer blocks [19]. In fact, the majority of successful experiments resulting in perpendicular cylinders, with the exception of ultra-thin films, use this method.…”
Section: Morphology Control Via Solvent Annealingmentioning
confidence: 99%